Technology Readiness Index (TRI) for Measurement of User Readiness in ERP Implementation in the Marketing Department - Afiana, Fiby; Septiana, Lisma Nur; Khotimah, Khusnul (Jurnal Sistem Informasi dan Ilmu Komputer, 2022)
Customer Relationship Management is part of the ERP System as one of the company's strategies to know and understand consumers as well as an approach that views consumers as the core of the company's business and success. PT. Selaras Hutama Mandiri (SHM) needs to analyze the readiness of Customer Relationship Management users with the aim of preventing failures during the implementation process which will have an impact on the company's business processes. By looking at the existing Human Resources, they are still unfamiliar with the use of technology, so it is feared that the technology to be adapted cannot be used by existing human resources. The method used is the Technology Readiness Index which refers to the tendency of users to adopt and use new technology in the work environment with the variables Optimism, Innovation, Discomfort and Insecurity. The results obtained that the independent variable that has an influence on the readiness of Customer Relationship Management users in operating or using Customer Relationship Management is the innovation variable with a value of sig .001 < from probability 0.05 and the t test has t count > t table, namely 5.916 < 2.365. Other independent variables Optimism, Discomfort and Insecurity did not affect users in operating or using Customer Relationship Management. Meanwhile, the independent variable simultaneously influences the dependent variable on the readiness of the Customer Relationship Management (Technology Readiness) users. So that the company' s concerns with the readiness and ability of employees to use technology can be overcome by an analysis using the Technology Readiness Index method that they are ready to use Customer Relationship Management. It is very important to analyze user readiness so that the technology applied to the company's business processes can be appropriate, meaning that technology implementation is not only a trend but in accordance with company needs. Keywords: ERP, CRM, TRI, User Readiness.